Seismic reliability of traditional and innovative concentrically braced frames. - Giugliano, Maria Teresa (Earthquake engineering & structural dynamics.)
Structural engineering problems are always affected by many sources of uncertainty, such as aleatory of material properties, applied loads and earthquake intensity, therefore, seismic assessment of structures should be based on probabilistic methods. Since PBSD (Performance-based Seismic Design) philosophy was formulated, many researches have been conducted in this field in order to develop simple and accurate procedures for evaluating structural reliability. An important contribution has been provided by Jalayer and Cornell, who have developed a closed form expression to evaluate the mean annual frequency of exceeding a defined limit state. In this paper, by assuming the record to record variability as the only source of uncertainty, the seismic reliability of concentrically braced frames designed according to traditional and innovative methodologies is investigated, and a comparison between their performances is presented. In particular, two design methodologies have been applied : Eurocode 8 provisions and a new design methodology based on a rigorous application of 'capacity design' criteria. The innovative reduced section solution strategy, based on the reduction of cross sections at bracing member ends, has also been analysed.